2013
DOI: 10.1111/1469-0691.12087
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of the seasonal effect on nasal carriage and the presence of Mycobacterium leprae in an endemic area in the general population

Abstract: Leprosy continues to be a significant health problem in certain pockets in developing countries. Better understanding of the transmission and source of the infection would help to decipher the transmission link, leading to control of the spread of the disease. The nose is considered to be a portal of entry, suggesting an aerial route for transmission through droplet infection. The evidence suggests that many individuals from endemic countries carry Mycobacterium leprae in their nasal cavities without having ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Studies have suggested that the population living in endemic areas with poor conditions is at highest risk for acquiring Mycobacterium leprae irrespective of season (Bhat & Prakash ; Lavania et al . ). Future studies, including field‐collected validation data (temperature, rivers, water sources, humidity), may help to identify the environmental factors associated with the incidence rate of leprosy.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have suggested that the population living in endemic areas with poor conditions is at highest risk for acquiring Mycobacterium leprae irrespective of season (Bhat & Prakash ; Lavania et al . ). Future studies, including field‐collected validation data (temperature, rivers, water sources, humidity), may help to identify the environmental factors associated with the incidence rate of leprosy.…”
Section: Discussionmentioning
confidence: 97%
“…[838485] Several studies in Indonesia, India, and Brazil have indicated that in an endemic community as population are exposed to infection, the biological samples such as blood, nasal swabs, saliva, and slit-skin smears of contacts of patients remain positive either for ML-specific antibody or for specific component of ML. [868788899091] How many of these biomarker-positive contacts of the population will transform into cases is generally uncertain and depends on the immune status of the individual having subclinical infection. These diagnostic tests are performed only once in individuals who pass through a dynamic state of the immune system, and therefore every individual who test positive to these assays do not develop leprosy in future.…”
Section: Leprae -Specific Antibody or Pcr Positivity In The Contexmentioning
confidence: 99%
“…The extraction and amplification of M. leprae DNA from nasal secretions can be very useful in both screening of potential contacts and leprosy control [43,49,85,88]. On the other hand, it has also demonstrated the importance of identifying healthy and subclinical carriers [50,83,84,87,[89][90][91][92]. In endemic countries, some studies have shown that there are no differences in being a nasal carrier of M. leprae DNA between contacts and non contacts (controls) of a leprosy patient [83,87].…”
Section: Suitable Samples For M Leprae Nucleic Acid Detectionmentioning
confidence: 99%
“…In endemic countries, some studies have shown that there are no differences in being a nasal carrier of M. leprae DNA between contacts and non contacts (controls) of a leprosy patient [83,87]. But, none of these studies have consistently associated the presence of the M. leprae DNA in nasal secretion with further development of the disease: it only indicates nasal carriage, which may imply active leprosy transmission [43,92].…”
Section: Suitable Samples For M Leprae Nucleic Acid Detectionmentioning
confidence: 99%
See 1 more Smart Citation